2012
DOI: 10.3109/0142159x.2012.680936
|View full text |Cite
|
Sign up to set email alerts
|

Features of educational interventions that lead to compliance with hand hygiene in healthcare professionals within a hospital care setting. A BEME systematic review: BEME Guide No. 22

Abstract: Background: In the United Kingdom, there are approximately 300,000 healthcare-associated infections (HCAI) annually, costing an estimated £1 billion. Up to 30% of all HCAI are potentially preventable by better application of knowledge and adherence to infection prevention procedures. Implementation of Department of Health guidelines through educational interventions has resulted in significant and sustained improvements in hand hygiene compliance and reductions in HCAI. Aim: To determine the features of struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 56 publications
0
51
0
1
Order By: Relevance
“…77,113 We identiÀ ed four systematic reviews of interventions to improve hand hygiene compliance. 77,[114][115][116] The most recent Cochrane review identiÀ ed 84 studies published after 2006 for potential inclusion, but only four studies (one RCT, two interrupted time series and one controlled before-after study) were included following detailed quality assessment. 77 The heterogeneity of interventions and methods precluded the pooling and meta-analysis of results, and it was concluded that multi-faceted campaigns that include social marketing or staff engagement may be more effective than campaigns without these components, and that education or product substitution alone were less effective.…”
Section: S21mentioning
confidence: 99%
“…77,113 We identiÀ ed four systematic reviews of interventions to improve hand hygiene compliance. 77,[114][115][116] The most recent Cochrane review identiÀ ed 84 studies published after 2006 for potential inclusion, but only four studies (one RCT, two interrupted time series and one controlled before-after study) were included following detailed quality assessment. 77 The heterogeneity of interventions and methods precluded the pooling and meta-analysis of results, and it was concluded that multi-faceted campaigns that include social marketing or staff engagement may be more effective than campaigns without these components, and that education or product substitution alone were less effective.…”
Section: S21mentioning
confidence: 99%
“…Three of the reviews published here (Cherry et al 2012;Nelson et al 2012;Steinert et al 2012) are the work of experienced BEME reviewers. They are testament to the developing scholarship of HPE systematic review methodology and the conviction that secondary research is of value to personal and community practice.…”
Section: The Latest Beme Reviewsmentioning
confidence: 95%
“…Both demonstrate the value of systematic review research. Whilst many might have known that, for example, 'repeated (education) sessions, fed into daily practice, will maintain compliance' (Cherry et al 2012) in the review, this is an evidence-supported key message and is all the more powerful because of the systematic and transparent work that led to that evidence.…”
Section: The Latest Beme Reviewsmentioning
confidence: 95%
See 1 more Smart Citation
“…[221][222][223][224] However, even in physiotherapists who had undertaken the training to deliver the ITE and TEA interventions, not all changes in intended clinical behaviour and attitudes and beliefs were maintained over the longer term (12-18 months after completing the training programme), a pattern seen in professional groups within other areas of health care. 225 There may be several reasons for this, including barriers at the level of the patient, the professional and the wider health-care organisation. Multimodal approaches that not only address the exercise attitudes and beliefs and intended behaviours of physiotherapists, but also identify and address other potential barriers to long-term behaviour change in physiotherapists, are likely to be required to achieve greater or more sustained changes in these variables over time.…”
Section: Number and Patterns Of Treatmentmentioning
confidence: 99%